If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + -30 = 15x + 12 Reorder the terms: -30 + 18x = 15x + 12 Reorder the terms: -30 + 18x = 12 + 15x Solving -30 + 18x = 12 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. -30 + 18x + -15x = 12 + 15x + -15x Combine like terms: 18x + -15x = 3x -30 + 3x = 12 + 15x + -15x Combine like terms: 15x + -15x = 0 -30 + 3x = 12 + 0 -30 + 3x = 12 Add '30' to each side of the equation. -30 + 30 + 3x = 12 + 30 Combine like terms: -30 + 30 = 0 0 + 3x = 12 + 30 3x = 12 + 30 Combine like terms: 12 + 30 = 42 3x = 42 Divide each side by '3'. x = 14 Simplifying x = 14
| 8f+19=19 | | 1+1+1+1+1+1+1+1+1+1+1+1*0+2= | | 6x-9=3x+6x | | 6-3b=-2-4b | | -2.3-6.6=-12.2-3.9 | | 3(3x-1)=4(3x-1) | | .10y-5=15 | | 10d+4+d=180 | | 45-3.5x=25 | | Y=4x-x-11 | | 16+.15x=.25x | | 14x-9=8+21x | | 13p-6=33 | | -9m-9=4 | | 30526-x=155528 | | 3(x+8)+14=2 | | 180=8x+120+7x | | 5b+15n=50 | | 6-.5x=10 | | -3y-9(3y-5)=-6+7(-7-y) | | 3x^2-13x-66=0 | | x+20+x-15+x-45=180 | | (0.6x^4)(0.2x^6)= | | 45+.25x=40+.30x | | 2(y-8)=6y-28 | | 40.25x=40+.30x | | .6x-6=7.2 | | 7u+4=3(u-4) | | 3(2x+4)=4+6x+12 | | -2(w+6)=-4w-16 | | Y-X=V | | 42=13+x+12 |